2013
DOI: 10.1371/journal.pone.0068967
|View full text |Cite|
|
Sign up to set email alerts
|

Ineffectiveness of Reverse Wording of Questionnaire Items: Let’s Learn from Cows in the Rain

Abstract: ObjectiveWe examined the effectiveness of reverse worded items as a means of reducing or preventing response bias. We first distinguished between several types of response bias that are often confused in literature. We next developed arguments why reversing items is probably never a good way to address response bias. We proposed testing whether reverse wording affects response bias with item-level data from the Multidimensional Fatigue Inventory (MFI-20), an instrument that contains reversed worded items.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
289
2
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(315 citation statements)
references
References 27 publications
14
289
2
10
Order By: Relevance
“…The lower value of alpha for baby factor may be due to the fact that it consists of both negatively and positively worded items. This result is consistent with recent evidences (37,38) against the previously recommended method of using the mixed item format (i.e. including both positively and negatively worded items) in scales (39).…”
Section: Discussionsupporting
confidence: 92%
“…The lower value of alpha for baby factor may be due to the fact that it consists of both negatively and positively worded items. This result is consistent with recent evidences (37,38) against the previously recommended method of using the mixed item format (i.e. including both positively and negatively worded items) in scales (39).…”
Section: Discussionsupporting
confidence: 92%
“…Item D19 loaded poorly onto both factors, consistent with increasing evidence of generally poor performance of reverse coded items (van Sonderen, Sanderman, & Coyne, 2013), and was dropped from further analysis. Notably, CDES8 exhibited cross-loadings onto both factors (.51 and .18 respectively), but as the second cross-loading was relatively small this item was retained pending further examination.…”
Section: Happiness Age and National Wealthmentioning
confidence: 85%
“…was discarded. As regards the reverse-coded items (also known as negatively worded items), researchers have suggested that these items may be a potential source of method bias (e.g., Podsakoff et al 2003), and the responses to these items could be contaminated by respondent's inattention and confusion (e.g., Van Sonderen et al 2013). Given the low item-total correlations of the negatively worded items (all correlation coefficients smaller than 0.4) and the presence of negative inter-item correlations between negatively worded items and positively worded items, these three negatively worded Intrinsic scale items were discarded.…”
Section: Methodsmentioning
confidence: 99%